Chronic immune-related adverse events arising from immune checkpoint inhibitors: an update - Douglas B Johnson; Kylie Fletcher (Journal for ImmunoTherapy of Cancer)
Immune checkpoint inhibitors (ICIs) have transformed cancer treatment, improving outcomes for many patients. However, toxicities termed immune-related adverse events (irAEs) are limitations of these revolutionary treatments. These irAEs may resolve with treatment or ICI cessation (acute) or persist many months beyond therapy cessation (chronic). Acute irAEs were the first to be recognized and are thus more well studied. However, chronic irAEs have been highlighted in recent years and are becoming a topic of more intensive investigation. These chronic irAEs have been noted to affect many different organ systems, including endocrine, rheumatologic, gastrointestinal, dermatologic, neurologic, and cardiovascular systems. In this review, we discuss current knowledge surrounding the frequency, time course, and risk factors associated with chronic irAEs affecting various organ systems, treatment approaches, and future directions.